Perancangan UI/UX Website Permohonan Cuti Pegawai Pada Diskominfo Sumatera Selatan Menggunakan Metode Design Thinking - Ikhsan Almi Irfansyah; Evi Fadilah (Prosiding, 2025)
The South Sumatra Provincial Communication and Informatics Office continues to experience challenges in its leave application process, which is considered inefficient. This process relies heavily on manual data processing, particularly in the personnel department, using physical documents and lacking the support of a centralized database. This often leads to errors in recording employee leave data. This study applies the Design Thinking method to improve the User Interface (UI) and User Experience (UX) through five stages: Empathize, Define, Ideate, Prototype, and Test. The purpose of designing the UI/UX for this leave application website is to minimize obstacles, reduce administrative errors, increase the efficiency of leave management by the agency, and facilitate more structured and effective documentation of employee leave data. Based on the results of testing conducted by distributing a System Usability Scale (SUS) questionnaire to five respondents, an average SUS score of 73 was obtained, which falls within the Acceptable category within the acceptance range. These results indicate that users responded positively to the application's ease of use